Pembuatan Branding Produk Untuk Mendukung Kegiatan Bulanan Jajanan Tradisional Ibu-Ibu PKK Desa Ekas Buana - Yulistia Nispi; Royyan Hayaza; Nirmala Sari; Lina Udayana; Nizham Kholid; Lalu Wahyu Andi Purnama (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
The PKK women's group in Ekas Buana village remains active in producing traditional snacks as an income-generating activity. However, these products are currently sold in plain, clear plastic packaging lacking logos, brand names, or product information, thereby failing to establish a distinct identity or appeal to consumers. This community service initiative aims to enhance the product's marketability and competitiveness by creating a logo and packaging design as a means of brand building. A participatory approach was employed, involving the PKK women in every stage of the process—from problem identification and analysis, observation, and design (logo and packaging) to consultation, printing, receipt of the final materials, and program implementation. The initiative resulted in a logo and packaging design that align with the product's characteristics while reflecting the unique identity of Ekas Buana village. Effective branding offers advantages by enhancing visual appeal, clarifying brand identity, and providing clear product information, ultimately making the products more competitive in the market. Evaluation results indicate a positive response from the partners, who have committed to using the new logo and packaging in future production activities. This program is expected to boost the marketing of these traditional snacks and strengthen their competitive edge.